Utilization of artificial nest boxes by house sparrow "Passer domesticus" in urban areas of Udhagamandalam, The Nilgiris, India - Jayaraman, Ariyappan; Ramakrishnan, Balasundaram; Samson, Arockianathan (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The study was conducted from June 2015 to May 2016 in the Udhangamandal urban areas of The Nilgiris, Tamil Nadu, India. Artificial nests were placed in three different habitats namely Market area, Residential area, and Institutional areas. In each study site 50 next boxes were erected which includes Wooden boxes (n = 10), Paper boxes (n = 10), Bamboo piece (n = 10), PVC pipes (n = 10) and Mud pots (n = 10).
Keywords: Artificial nest boxes; House Sparrows; Udhagamandalam; Nilgiris; Tamil Nadu; India